2023
DOI: 10.1007/s11064-023-03878-z
|View full text |Cite
|
Sign up to set email alerts
|

β-lapachone-mediated WST1 Reduction as Indicator for the Cytosolic Redox Metabolism of Cultured Primary Astrocytes

Abstract: Electron cycler-mediated extracellular reduction of the water-soluble tetrazolium salt 1 (WST1) is frequently used as tool for the determination of cell viability. We have adapted this method to monitor by determining the extracellular WST1 formazan accumulation the cellular redox metabolism of cultured primary astrocytes via the NAD(P)H-dependent reduction of the electron cycler β-lapachone by cytosolic NAD(P)H:quinone oxidoreductase 1 (NQO1). Cultured astrocytes that had been exposed to β-lapachone in concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…1 – 3 ). To test for a potential release of pyruvate from astrocytes that had been exposed to other metabolic substrates than glucose, the cells were incubated for 5 h in 250 µL glucose-free buffer that had been supplemented with 5 mM of other hexoses or known mitochondrial substrates [ 18 , 33 , 60 ]. Compared to glucose-fed astrocytes, almost identical extracellular pyruvate concentrations were found for cells that had been exposed to mannose or lactate, but the cell established also in the presence of fructose, sorbitol or alanine extracellular pyruvate concentrations that were significantly higher than those determined for the substrate-free incubation (None) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 – 3 ). To test for a potential release of pyruvate from astrocytes that had been exposed to other metabolic substrates than glucose, the cells were incubated for 5 h in 250 µL glucose-free buffer that had been supplemented with 5 mM of other hexoses or known mitochondrial substrates [ 18 , 33 , 60 ]. Compared to glucose-fed astrocytes, almost identical extracellular pyruvate concentrations were found for cells that had been exposed to mannose or lactate, but the cell established also in the presence of fructose, sorbitol or alanine extracellular pyruvate concentrations that were significantly higher than those determined for the substrate-free incubation (None) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An additional pathway that may contribute to the disappearance of 2DG6P from cultured astrocytes is the oxidation In panel (c), the significance of differences (t-test) between the data obtained for incubations in the absence and the presence of 2DG is indicated by # p < 0.05 and ## p < 0.01 of 2DG6P by G6PDH, as 6-phospho-2-deoxygluconate has been found in the brain of 2DG-exposed rats [4]. We have previously shown that cellular NADPH regeneration via the PPP can be studied by monitoring the NQO1-dependent reduction of extracellular WST1 to its formazan in the presence of the redox cycler β-lapachone [26,42]. In the presence of 2DG the glucose-independent WST1 reduction was almost doubled in a concentration-dependent manner by 2DG, suggesting that 2DG6P acts as substrate of G6PDH in living astrocytes, thereby providing electrons via NADPH for the WST1 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…To test for the consequences of a high cellular concentration of 2DG6P on the NADPH regeneration by the PPP of astrocytes, the PPP-and NADPH-dependent WST1 reduction was investigated in the absence and the presence of glucose in the experimental paradigm previously described In panel (c), the significance of differences (t-test) between data from incubations in the absence or the presence of 2DG for the given incubation periods (black vs. green and red vs. yellow) is indicated by # p < 0.05, ## p < 0.01 and ### p < 0.001. Significant differences between data for the two different incubations periods of each condition (with or without 2DG preincubation, black vs. red and green vs. yellow) are indicated by + p < 0.05 and ++ p < 0.01 [26,42]. After the 30 min preincubation of astrocytes in the presence of 2DG, the cells contained a specific 2DG6P content of 130.6 ± 9.1 nmol/mg.…”
Section: Consequences Of a Pre-loading Of Astrocytes With 2dg6p On Th...mentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the specific inhibitor G6PDi−1 prevented neuronal death caused by the expression of mutated SOD1 or TDP43 proteins in a model of amyotrophic lateral sclerosis, indicating a beneficial effect of G6PDH activity on cells in pathological conditions [42]. Results from a study on cultured astrocytes demonstrated that G6PDi−1 (10 µM) inhibited 60% of the supply of electrons for a NQO1-catalysed β-lapachone-mediated reduction in the water-soluble tetrazolium salt 1, suggesting that NADPH, derived from PPP, is the main source of electrons for cytosolic NAD(P)H quinone oxidoreductase 1 (NQO1) [43]. Importantly, another study from this group provided compelling evidence that G6PDi−1 efficiently and specifically inhibits astrocytic G6PDH without affecting other oxidoreductases, indicating that G6PDi−1 is a suitable and specific tool for inhibiting G6PDH and PPP-dependent processes [44].…”
Section: Effect Of G6pdi−1 On Glucose Consumption Induced By Shaffer ...mentioning
confidence: 99%